The Implementation of Recitation Method in Persuasive Speech Learning Using Indonesian Language Textbooks - Lailatussobaria, Rinda; Muslimin; Sartika, Eka (Raja Zulkarnain Education Foundation, 2025)
This study aims to describe: 1) the application of the recitation method in learning persuasive speech for grade IX students at MTs Al-Ikhlas Bilungala, 2) supporting and inhibiting factors when applying the recitation method in learning persuasive speech for grade IX students at MTs Al-Ikhlas Bilungala. This study was conducted from February to April 2025. The population and sample of the study consisted of 30 grade IX students from MTs Al-Ikhlas Bilungala, as well as data and sources on persuasive speech skills of grade IX students and Indonesian language teachers. The data collection techniques employed were observation, interviews, documentation, and questionnaires. The data analysis techniques employed in this study included data collection, data reduction, data display, and drawing conclusions. Research results: 1) The application of the recitation method in learning persuasive speech for grade IX students at MTs Al-Ikhlas Bilungala, using national textbooks, is divided into three activities: preliminary activities, core activities, and the implementation of core activities. There is an application of the recitation method consisting of the assignment phase, the task implementation phase, the task accountability phase, and closing activities; the application of the recitation method carried out is also classified as very good with a percentage of 73% through student response questionnaire data; 2) supporting factors come from facilities and infrastructure as well as students' interests and attention and reading skills in subject matter while inhibiting factors come from the teacher's difficulty in controlling student honesty and the inaccuracy of time in collecting assignments.